1980
DOI: 10.1037/h0081061
|View full text |Cite
|
Sign up to set email alerts
|

Twin–singleton language differences.

Abstract: Differences on 13 child language variables were investigated for 12 sels of 24-ycar-old twins and 24 singletons, matched lor age and socioeconomic stains. Two-hour spontaneous speech records were obtained in the home. A regression analysis assessed the contribution of the biological (perinatal) and maternal speech variables to the child language measures. Rate of mother's speech to child was the most important predictor of child language performance. Singletons talked more, addressed more utterances to iheir m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
74
0
5

Year Published

1987
1987
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 20 publications
1
74
0
5
Order By: Relevance
“…Of interest, this finding calls into question the common notion that twins tend to have less advanced language skills compared with singletons. Perhaps reported delays are most pronounced at younger ages (Conway et al, 1980;Hay et al, 1987;Rutter et al, 2003). The third form of evidence supporting the validity of the language sample measures is the consistent mean differences favoring children without a history of expressive language difficulties compared with those who have a reported history of expressive difficulties.…”
Section: Discussionmentioning
confidence: 84%
“…Of interest, this finding calls into question the common notion that twins tend to have less advanced language skills compared with singletons. Perhaps reported delays are most pronounced at younger ages (Conway et al, 1980;Hay et al, 1987;Rutter et al, 2003). The third form of evidence supporting the validity of the language sample measures is the consistent mean differences favoring children without a history of expressive language difficulties compared with those who have a reported history of expressive difficulties.…”
Section: Discussionmentioning
confidence: 84%
“…It has generally been believed that the language development of twins is delayed in comparison with that of singletons because of their low birth weight and postnatal language learning environment -immaturity of physical development and reduced individual conversation with their mother (1)(2)(3)(4)(5)(6)(7)(8). However, a recent study suggested that 'twin language' affects their delay of normal language development (9).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the prevalence of persisting difficulties was 16% for articulation, 12% for expressive language, and 3% for receptive language. Consequently, in comparison to the singleton literature, rates of speech-language difficulties in the present twin sample appeared somewhat higher.Higher rates of speech-language difficulties in twins are likely due to higher rates of the same risk factors that contribute to speech-language difficulties in singletons, specifically biological factors, such as prematurity, lower birth weight, and so forth (Field, Dempsey, & Shuman, 1981;Luke & Keith, 1992), and social factors, such as less individualized parental interaction (e.g., Conway, Lytton, & Pysh, 1980;Thorpe, Rutter, & Greenwood, 2003). In part because of these risk factors, twins often receive more frequent professional vigilance, which may in turn make communication difficulties more likely to be identified than in singleton children.…”
mentioning
confidence: 99%